2015
DOI: 10.4238/2015.january.23.3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and association of single-nucleotide polymorphisms in gonadotropin-inhibitory hormone (GnIH) gene with egg production traits in Erlang mountainous chickens

Abstract: ABSTRACT. Gonadotropin-inhibitory hormone (GnIH) gene is an important gene in reproduction. In this study, we screened singlenucleotide polymorphisms (SNPs) in the chicken GnIH gene among 204 individuals in Erlang mountainous chickens. We then analyzed the associations between polymorphisms of the GnIH gene and 5 egg production traits in chickens. Five SNPs (T3305C, T3310C, G3403C, G3411A, and T3591C) were detected. Associations between polymorphic loci and age at first egg, body weight at first egg, weight at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Five SNPs were detected. There were significant associations between polymorphic loci and age at first egg, body weight at first egg and egg production in 300 days (Hu et al, 2015). Lima et al (2014) reported that there is a three-nucleotide in frame deletion in the human GnIH precursor gene (p.I71_K72), with a smaller proportion in the idiopathic central precocious puberty (CPP) (5%) compared to the normosmic isolated hypogonadotrophic hypogonadism (nIHH) (15%) group.…”
Section: Polymorphisms In Gnih Precursor Genementioning
confidence: 97%
See 1 more Smart Citation
“…Five SNPs were detected. There were significant associations between polymorphic loci and age at first egg, body weight at first egg and egg production in 300 days (Hu et al, 2015). Lima et al (2014) reported that there is a three-nucleotide in frame deletion in the human GnIH precursor gene (p.I71_K72), with a smaller proportion in the idiopathic central precocious puberty (CPP) (5%) compared to the normosmic isolated hypogonadotrophic hypogonadism (nIHH) (15%) group.…”
Section: Polymorphisms In Gnih Precursor Genementioning
confidence: 97%
“…Genetic variations are commonly found in the DNA between the genes, but SNPs within a gene or in a regulatory region may directly affect the gene's function. Hu et al (2015) screened SNPs in the chicken GnIH precursor gene among 204 individuals in Erlang mountainous chickens. They further analyzed the associations between polymorphisms in the GnIH precursor gene and egg production traits.…”
Section: Polymorphisms In Gnih Precursor Genementioning
confidence: 99%
“…Peng L. (2013) detected AA, AB and BB genotypes on GR1 segment of intron 2 of GnRHR gene in muscovy duck, which all showed significant correlations with laying start age, maximum number of continuous laying days, average number of continuous laying days and egg number of 300-day old ducks. Hu et al (2015) pointed out that 3 SNPs of GnRH gene influenced laying start age of Erlangshan chicken significantly and SNP5 played an important role in body weight at the beginning of laying. All these studies show that GnRH gene might regulate the production performance of poultry.…”
Section: Association Analysis Between Gnrh Gene and Growth Traitsmentioning
confidence: 99%
“…For mutation site T68G of GnRH gene detected in Rongjiang little sweet sheep, lambing number of GG genotype was far higher than those of the rest two genotypes (P<0.05) (Li et al 2016). That 3 SNPs of GnRH gene influenced laying start age of Erlangshan chicken significantly and SNP5 played an important role in body weight at beginning of laying (Hu et al 2015). All These studies showed that GnRH gene could regulate the production performance of poultry.…”
Section: Association Analysis Between Gnrh Gene and Carcass Traitsmentioning
confidence: 86%